Over-the-top business models for the sports broadcasting industry: sports rights owners going over-the-top with direct-to-consumer streaming services - an in-depth analysis - Pohlücke, Lennart Mathis (2021)
Sports-rights-owners are increasingly bringing owned and operated Over-The-Top streaming platforms to the market. This report investigates the impact the operation of a Direct-to-Consumer streaming platform has on their business model. The vertical for ward integration causes a significant shift in the business model. By becoming media companies and operating in the downstream broadcasting market, rights owners are facing segmentation challenges, must engage in new activities and need to develop a new set of capabilities, related to an increased cost structure. In addition, the financial stability underlies an increased risk, as stable licensing revenues are being replaced with more volatile revenue sources.